2000
DOI: 10.1091/mbc.11.8.2631
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Peroxidase Is Required for the Transcriptional Response to Oxidative Stress in Budding Yeast

Abstract: A genetic screen was performed in Saccharomyces cerevisiae to identify mechanisms important for the transcriptional activation of genes encoding antioxidant proteins. Thioredoxin peroxidase, Tsa1p, of the thioredoxin system, was found to be essential for the transcriptional induction of other components of the thioredoxin system, TRX2 (thioredoxin) and TRR1 (thioredoxin reductase), in response to H(2)O(2). The expression of TRX2 and TRR1 is known to be regulated by the transcription factors Yap1p and Skn7p in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 35 publications
1
68
1
2
Order By: Relevance
“…For this reason, because of the presence of a response regulator domain and because of its involvement in a number of important but seemingly unrelated cellular processes, the protein has attracted considerable interest. Skn7p has been implicated in cell cycle control (59,392), the oxidative stress response (90,91,267,296,297,324,325,337,390,516), the heat shock response (487), cell wall metabolism (70,282,338), and nitrogen starvation-induced diploid filamentous growth (349). Genetic and physical interactions link Skn7p not only to the HOG pathway (164, 281, 337, 591) but also to cell cycle-dependent transcription (59,391,392), the cell integrity pathway (5, 69), the heat shock transcription factor (487), the Yap1p oxidative stress transcription factor (91,324,390,516), and calcineurin-dependent signaling (648).…”
Section: Skn7p: Integrating Input From Differentmentioning
confidence: 99%
“…For this reason, because of the presence of a response regulator domain and because of its involvement in a number of important but seemingly unrelated cellular processes, the protein has attracted considerable interest. Skn7p has been implicated in cell cycle control (59,392), the oxidative stress response (90,91,267,296,297,324,325,337,390,516), the heat shock response (487), cell wall metabolism (70,282,338), and nitrogen starvation-induced diploid filamentous growth (349). Genetic and physical interactions link Skn7p not only to the HOG pathway (164, 281, 337, 591) but also to cell cycle-dependent transcription (59,391,392), the cell integrity pathway (5, 69), the heat shock transcription factor (487), the Yap1p oxidative stress transcription factor (91,324,390,516), and calcineurin-dependent signaling (648).…”
Section: Skn7p: Integrating Input From Differentmentioning
confidence: 99%
“…Unlike deletion of the thioredoxin/thioredoxin reductase encoding genes, studies have shown that deletion of the TSA1 gene has no obvious a ect on the nuclear localization of Yap1 Delaunay et al, 2000;Ross et al, 2000) or on the basal level expression of Yap1 target genes, TRX2 and TRR1 (Delaunay et al, 2000;Ross et al, 2000); although there is one con¯icting report that suggests an increase in basal level expression of Yap1-dependent genes in a tsa1 strain . In contrast, in response to very low levels of H 2 O 2 (0.1 mM), induction of TRX2 and TRR1 is much reduced in a tsa1 strain while overexpression of TSA1 results in faster than normal induction of TRX2 and TRR1 (Ross et al, 2000). Furthermore, in S. pombe, Tsa1 appears to be required for the induction of Pap1-regulated gene expression in response to H 2 O 2 (Findlay et al, 2001, unpublished observation).…”
Section: Thioredoxin Dependent Deactivation Of Yap-1mentioning
confidence: 99%
“…TPx is not only involved in direct detoxification of reactive peroxides. In yeast it was found that at least one TPx-1 orthologue is essential for launching off the cellular response to oxidative stress (30), a process that is based on up-and downregulation of numerous gene activities. DmTPx-1 belongs to a group of proteins in Drosophila that are differentially expressed in the developmental stages of Drosophila (21).…”
Section: Fig 1 Western Blot Of Recombinant and Wild-type Dmtrx-2mentioning
confidence: 99%